Is It Possible to Train the Focus on Positive and Negative Parts of One’s Own Body? A Pilot Randomized Controlled Study on Attentional Bias Modification Training - Engel, Nicole; Waldorf, Manuel; Hartmann, Andrea; Voßbeck-Elsebusch, Anna; Vocks, Silja (Frontiers in Psychology, 2019)
Dysfunctional body- and shape-related attentional biases are involved in the etiology and maintenance of eating disorders (ED). Various studies suggest that women, particularly those with ED diagnoses, focus on negatively evaluated parts of their own body, which leads to an increase in body dissatisfaction. The present study aims to empirically test the hypothesis that non-ED women show an attentional bias toward negative body parts and that the focus on positive and negative parts of one’s own body can be modified by attentional bias modification training based on a dot-probe task. Although several studies have measured body-related attentional biases by using pictures of participants’ own bodies, the approach of investigating attentional bias via a dot-probe task while presenting pictures of the participants’ own body parts and modifying the biased attention using such pictures is novel. Women (n = 60) rank-ordered 10 parts of their own body regarding their attractiveness. To examine and modify the attentional focus, pictures of the self-defined positive and negative parts of one’s own body were presented by means of a dot-probe task. A paired-sample t-test revealed no difference between reaction times to negative compared to positive body parts, indicating no attentional bias toward negative parts of one’s own body. A two-way ANOVA revealed a main effect of time for pictures of positive and negative parts of one’s own body, with a decrease in reaction times from pre- to post-training. However, there was no significant interaction between time and training condition concerning reaction times to positive and negative body parts. Our findings replicate previous evidence of a balanced attentional pattern regarding one’s own body in women without ED diagnoses. However, the dot-probe task failed to modify the attentional focus. As the modifiability of state body image increases with more pronounced body dissatisfaction, the next step would be to test this approach in clinical samples of women with ED diagnoses.